Corrugation Enabled Asymmetrically Ultrastretchable (95%) Monocrystalline Silicon Solar Cells with High Efficiency (19%). Issue 45 (16th October 2019) - El‐Atab, Nazek; Qaiser, Nadeem; Bahabry, Rabab; Hussain, Muhammad Mustafa
Abstract: Stretchable solar cells are of growing interest due their key role in realizing many applications such as wearables and biomedical devices. Ultrastretchability, high energy‐efficiency, biocompatibility, and mechanical resilience are essential characteristics of such energy harvesting devices. Here, the development of wafer‐scale monocrystalline silicon solar cells with world‐record ultrastretchability (95%) and efficiency (19%) is demonstrated using a laser‐patterning based corrugation technique. The demonstrated approach transforms interdigitated back contacts (IBC) based rigid solar cells into mechanically reliable but ultrastretchable cells with negligible degradation in the electric performance in terms of current density, open‐circuit voltage, and fill factor. The corrugation method is based on the creation of alternating grooves resulting in silicon islands with different shapes. The stretchability is achieved by orthogonally aligning the active silicon islands to the applied tensile stress and using a biocompatible elastomer (Ecoflex) as a stretchable substrate. The resulting mechanics ensure that the brittle silicon areas do not experience significant mechanical stresses upon asymmetrical stretching. Different patterns are studied including linear, diamond, and triangular patterns, each of which results in a different stretchability and loss of active silicon area. Finally, finite element method based simulation is conducted to study the generated deformation in the different patterned solar cells. Abstract : Asymmetrically ultrastretchable wafer‐scale monocrystalline silicon solar cells with world record ultrastretchability (95%) and efficiency (19%) are fabricated using a laser‐patterning based corrugation technique applied on commercial solar cells with interdigitated‐back‐contacts. The stretchability is achieved by using a biocompatible elastomer (Ecoflex) as a stretchable encapsulant and by orthogonally aligning the active corrugated silicon islands to the applied tensile stress.